Linguistic Analysis and Phenomenology - Mays, Wolfe. author. aut Link
VIII, 307 p.
Keywords: This volume contains the proceedings of the six symposia of the 'Philosophers into Europe' conference held under he joint auspices of the Royal Institute of Philosophy and the British Society for Phenomenology at the University of Southampton in September 1969.